COMPARATIVE STUDY OF E-GOVERNMENT ENTERPRISE ARCHITECTURE BY PRIMARY ATTRIBUTES OF 3 ASIAN COUNTRIES - Khakim Ghozali; Yudho Giri Sucahyo (Faculty of Computer Science Universitas Indonesia, 2012)
By Waseda University International e-Government Ranking, announced in 2012 the state of Singapore and Korea ranks first and third in the implementation of e-government. Whereas Indonesia ranks 33[6]. This study aims to conduct a comparative analysis of the implementation of e-government Enterprise Architecture in Korea, Singapore and Indonesia. Stages of the research conducted is reviewing literature on TOGAF framework, define the attribute comparison, analysis of EA implementation in each country and do a comparison of the EA of both countries. Attributes used for comparison EA are business architecture, information systems architecture and technology architecture. Korea and Singapore divide business area into two business areas, namely public services and support services. Indonesia has tthree business area. Korea split by sector information system development while Singapore users group split based information system. Indonesia has 4 main application. Korea emphasizing mobile technology and the common component. While Singapore visible effort to increase the use of middleware. Indonesian technology solutions that enable information used accessed through various devices.